Bounding Global Aerosol Radiative Forcing of Climate Change. (16th March 2020) - Bellouin, N.; Quaas, J.; Gryspeerdt, E.; Kinne, S.; Stier, P.; Watson‐Parris, D.; Boucher, O.; Carslaw, K. S.; Christensen, M.; Daniau, A.‐L.; Dufresne, J.‐L.; Feingold, G.; et al.
Abstract: Aerosols interact with radiation and clouds. Substantial progress made over the past 40 years in observing, understanding, and modeling these processes helped quantify the imbalance in the Earth's radiation budget caused by anthropogenic aerosols, called aerosol radiative forcing, but uncertainties remain large. This review provides a new range of aerosol radiative forcing over the industrial era based on multiple, traceable, and arguable lines of evidence, including modeling approaches, theoretical considerations, and observations. Improved understanding of aerosol absorption and the causes of trends in surface radiative fluxes constrain the forcing from aerosol‐radiation interactions. A robust theoretical foundation and convincing evidence constrain the forcing caused by aerosol‐driven increases in liquid cloud droplet number concentration. However, the influence of anthropogenic aerosols on cloud liquid water content and cloud fraction is less clear, and the influence on mixed‐phase and ice clouds remains poorly constrained. Observed changes in surface temperature and radiative fluxes provide additional constraints. These multiple lines of evidence lead to a 68% confidence interval for the total aerosol effective radiative forcing of ‐1.6 to ‐0.6 W m −2, or ‐2.0 to ‐0.4 W m −2 with a 90% likelihood. Those intervals are of similar width to the last Intergovernmental Panel on Climate Change assessment but shifted toward more negative values. The uncertainty will narrow in the future by continuing to critically combine multiple lines of evidence, especially those addressing industrial‐era changes in aerosol sources and aerosol effects on liquid cloud amount and on ice clouds. Plain Language Summary: Human activities emit into the atmosphere small liquid and solid particles called aerosols. Those aerosols change the energy budget of the Earth and trigger climate changes, by scattering and absorbing solar and terrestrial radiation and playing important roles in the formation of cloud droplets and ice crystals. But because aerosols are much more varied in their chemical composition and much more heterogeneous in their spatial and temporal distributions than greenhouse gases, their perturbation to the energy budget, called radiative forcing, is much more uncertain. This review uses traceable and arguable lines of evidence, supported by aerosol studies published over the past 40 years, to quantify that uncertainty. It finds that there are two chances out of three that aerosols from human activities have increased scattering and absorption of solar radiation by 14% to 29% and cloud droplet number concentration by 5 to 17% in the period 2005–2015 compared to the year 1850. Those increases exert a radiative forcing that offsets between a fifth and a half of the radiative forcing by greenhouse gases. The degree to which human activities affect natural aerosol levels, and the response of clouds, and especially ice clouds, to aerosol perturbations remain particularly uncertain. Key Points: An assessment of multiple lines of evidence supported by a conceptual model provides ranges for aerosol radiative forcing of climate change Aerosol effective radiative forcing is assessed to be between ‐1.6 and ‐0.6 W m −2 at the 16–84% confidence level Although key uncertainties remain, new ways of using observations provide stronger constraints for models